“Engel Pharmacy “La Coróna”, near the gate of the royal court, Jassy”* - GRUIA, Ana-Maria (Studia Universitatis Babeș-Bolyai Historia, 2021)
The paper reconstructs the history of the 19th-20th-century Engel pharmacy in Iaşi starting from a lot of items preserved in the History of Pharmacy Collection in Cluj-Napoca. The lot includes numerous drug jars, measuring cups, apothecary working tools, financial documents, prescriptions, correspondence, and various other documents, some of which were recently identified during the renovation of the pharmacy museum in Cluj. The analysis allows one to see the transformation of pharmaceutical practice in Moldavia and Romania between the end of the 19th century and the Second World War and to reconstruct the history of a successful family business. Article history: Received 14.10.2021; Revised 26.11.2021; Accepted 18.12.2021; Available online 13.04.2022. Rezumat: “Farmacia Engel “La Coróna”, lângă poarta curţii domneşti, Jassy”. Articolul reconstituite istoria farmaciei Engel din Iaşi din secolele XIX-XX pornind de la un lot de obiecte păstrate în Colecţia de Istorie a Farmaciei din Cluj-Napoca. Lotul constă din numeroase recipiente farmaceutice, mensuri, unelte specifice meseriei, documente financiare şi contabile, reţete, corespondenţă şi diverse alte documente şi tipărituri. Unele bunuri au fost reidentificate recent, cu ocazia lucrărilor de renovare ale muzeului de istorie a farmaciei din Cluj. Analiza permite observarea transformărilor practicii farmaceutice din Moldova şi România între sfârşitul secolului al XIX-lea şi Cel de Al Doilea Război Mondial, dar şi refacerea istoriei unei reuşite afaceri de familie. Cuvinte cheie: istoria farmaciei, Iaşi, studii muzeale, familia Engel